Increased Knowledge of Pregnant Women about the Importance of Micro Minerals (Fe) During Pregnancy - Sebayang, Nico Syahputra; Nopitasari, Iin; Saragih, Pestaria; Alhanannasir, Alhanannasir (Altifani Journal: International Journal of Community Engagement, 2021)
Micro minerals (Fe) are indispensable for every woman, especially during pregnancy. The need for micro minerals (Fe) increases with increasing gestational age. Micro minerals (Fe) are not only important for pregnant women, they are also important for babies in the womb. Deficiency of micro minerals (Fe) can increase the risk of giving birth to babies with low body weight or premature birth and even maternal and infant mortality. If the baby is born with a normal weight, but there is still the possibility of stunting (short children). The purpose of this community service is to increase the knowledge of pregnant women about the importance of consuming micro minerals (Fe) during pregnancy. Knowledge of pregnant women in Sungai Rengit Murni village about the consumption of micro minerals (Fe) can be said to be quite good, reaching 70% of the total number of pregnant women (statement of regional midwives). We hope that as a servant, with this community service program, it is hoped that the knowledge of pregnant women about the importance of consuming micro minerals (Fe) during pregnancy will increase. So that the risk that will occur to the mother and baby is reduced. In addition, the service also supports government programs in reducing maternal problems during pregnancy until delivery.